The Diminution of R‐Loops Generated by LncRNA DSP‐AS1 Inhibits DSP Gene Transcription to Impede the Re‐Epithelialization During Diabetic Wound Healing - Chen Yang; Hong Lian; Hengli Luo; Chenlin Song; Jianghong Lin; Zhuoxian Liang; Yulin Yang; Xiaosi Hong; Shaohua Li; Yanbo Chen; Liangyan Wu; Li Yan; et al. (Advanced Science)
Abstract Re‐epithelialization constitutes a critical stage in the intricate process of wound healing, yet its mechanisms in the context of diabetic wounds remain elusive. In this study, the role of the mesenchymal‐epithelial transition (MET) vis‐à‐vis the epithelial‐mesenchymal transition (EMT) of keratinocytes in diabetic wound re‐epithelialization is investigated. The findings reveal an impediment in the MET process, rather than EMT, which significantly compromised re‐epithelialization in diabetic wounds. Furthermore, Desmoplakin (DSP) gene expression, encoding a key desmosome protein, is down‐regulated in diabetic rats. This down‐regulation coincided with aberrant hypo‐demethylation of the DSP promoter. The inhibition of DSP expression is linked to reduced occupancy of Ten‐eleven translocation 3 (TET3) at the DSP promoter, consequently suppressing TET3‐dependent DNA demethylation. Additionally, a novel lncRNA termed DSP‐AS1is identified, which is antisense to DSP. Notably, DSP‐AS1 expression is down‐regulated in diabetic skin wounds, and it interacted with TET3, a DNA demethylase. Notably, DSP‐AS1 is found to form R‐loops, triple‐stranded DNA:RNA hybrids, at the DSP promoter, facilitating TET3 localization to the DSP promoter. Collectively, the findings suggest that reduced R‐loop formation by DSP‐AS1 impairs DSP gene transcription by repressing TET3‐mediated DNA demethylation. This disruption of the orchestrated re‐epithelialization process contributes to refractory diabetic wound healing.